2013
DOI: 10.1002/smll.201302084
|View full text |Cite
|
Sign up to set email alerts
|

Direct Intermolecular Force Measurements between Functional Groups and Individual Metallic or Semiconducting Single‐Walled Carbon Nanotubes

Abstract: Many electronic applications of single-walled carbon nanotubes (SWNTs) require electronic homogeneity in order to maximally exploit their outstanding properties. Non-covalent separation is attractive as it is scalable and results in minimal alteration of nanotube properties. However, fundamental understanding of the metallicity-dependence of functional group interactions with nanotubes is still lacking; this lack is compounded by the absence of methods to directly measure these interactions. Herein, a novel te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The commonality between the CR and SANS molecules is that they both contain naphthalene–sulfonate groups. The naphthalene rings enhance the adsorption of met-SWNTs onto the beads due to the π–π stacking between the free electrons of the aromatic rings and extended π electrons in the more polarizable met-SWNTs. , The SANS modification results in higher-purity sorting than the CR modification (Figure A) because the simple naphthalene-sulfonate structure of SANS avoids the complicated and unknown effects from the conjugated azo bonds and the primary amine groups of the CR molecules.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The commonality between the CR and SANS molecules is that they both contain naphthalene–sulfonate groups. The naphthalene rings enhance the adsorption of met-SWNTs onto the beads due to the π–π stacking between the free electrons of the aromatic rings and extended π electrons in the more polarizable met-SWNTs. , The SANS modification results in higher-purity sorting than the CR modification (Figure A) because the simple naphthalene-sulfonate structure of SANS avoids the complicated and unknown effects from the conjugated azo bonds and the primary amine groups of the CR molecules.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The detailed growth condition can be found in the Methods Section. The nanoscale mechanical behaviors have been studied using Quantitative Nanomechanical Property Mapping (QNM) technique based on the AFM setup with a spatial resolution better than 10 nm [35][36][37] . The effective modulus is calculated by extrapolating the retraction curve close to the contact point and using a Derjaguin-Muller-Toporov (DMT) model 38 as shown in supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The AFM probe functionalization procedure is the same as that of the reported . Gold coated AFM probes (Multi75GB-G, Budget Sensors) were cleaned by immersing in hot Piranha solution for 90 s and then rinsing extensively with DI water followed by either ethanol (absolute), N , N -dimethylformamide (DMF), or DI water (depending on the functionalization to be performed) and then drying under Ar.…”
Section: Methodsmentioning
confidence: 99%
“…Chemical force microscopy (CFM), which is a variation of the atomic force microscopy (AFM), is a versatile technique for exploring the interfacial interactions between two surfaces. , Previously, we have shown that CFM technique is sensitive enough to differentiate the noncovalent interaction forces between a functionalized CFM tip and M SWNTs versus S SWNTs …”
Section: Introductionmentioning
confidence: 99%